Controlled Release of Epigenetically-Enhanced Extracellular Vesicles from a GelMA/Nanoclay Composite Hydrogel to Promote Bone Repair - Man, Kenny; Barroso, Inês A.; Brunet, Mathieu Y.; Peacock, Ben; Federici, Angelica S.; Hoey, David A.; Cox, Sophie C. (International journal of molecular sciences, 2022)
Extracellular vesicles (EVs) have garnered growing attention as promising acellular tools for bone repair. Although EVs’ potential for bone regeneration has been shown, issues associated with their therapeutic potency and short half-life in vivo hinders their clinical utility. Epigenetic reprogramming with the histone deacetylase inhibitor Trichostatin A (TSA) has been reported to promote the osteoinductive potency of osteoblast-derived EVs. Gelatin methacryloyl (GelMA) hydrogels functionalised with the synthetic nanoclay laponite (LAP) have been shown to effectively bind, stabilise, and improve the retention of bioactive factors. This study investigated the potential of utilising a GelMA-LAP hydrogel to improve local retention and control delivery of epigenetically enhanced osteoblast-derived EVs as a novel bone repair strategy. LAP was found to elicit a dose-dependent increase in GelMA compressive modulus and shear-thinning properties. Incorporation of the nanoclay was also found to enhance shape fidelity when 3D printed compared to LAP-free gels. Interestingly, GelMA hydrogels containing LAP displayed increased mineralisation capacity (1.41-fold) (p ≤ 0.01) over 14 days. EV release kinetics from these nanocomposite systems were also strongly influenced by LAP concentration with significantly more vesicles being released from GelMA constructs as detected by a CD63 ELISA (p ≤ 0.001). EVs derived from TSA-treated osteoblasts (TSA-EVs) enhanced proliferation (1.09-fold), migration (1.83-fold), histone acetylation (1.32-fold) and mineralisation (1.87-fold) of human bone marrow stromal cells (hBMSCs) when released from the GelMA-LAP hydrogel compared to the untreated EV gels (p ≤ 0.01). Importantly, the TSA-EV functionalised GelMA-LAP hydrogel significantly promoted encapsulated hBMSCs extracellular matrix collagen production (≥1.3-fold) and mineralisation (≥1.78-fold) in a dose-dependent manner compared to untreated EV constructs (p ≤ 0.001). Taken together, these findings demonstrate the potential of combining epigenetically enhanced osteoblast-derived EVs with a nanocomposite photocurable hydrogel to promote the therapeutic efficacy of acellular vesicle approaches for bone regeneration.